Â¹Mahasiswa Penulis Skripsi Prodi Pendidikan Tata Rias dan Kecantikan untuk Wisuda Periode 109 September 2017 Â²Pembimbing I, Dosen Jurusan Tata Rias dan Kecantikan Fakultas Pariwisata dan Perhotelan UNP 3 Pembimbing II, Dosen Jurusan Tata Rias dan Kecantikan Fakultas Pariwisata dan Perhotelan UNP 1 PENGARUH PENGGUNAAN MASKER BUAH SEMANGKA TERHADAP KULIT WAJAH KERING - Prima, Nadia; Rahmiati, Rahmiati; Astuti, Murni (Journal of Home Economics and Tourism, 2017)
The aim of this research is to analyze the influence of White Skin Fruit Mask to overcome dry skin based on indicator of moisture and brightness of facial skin. This research is an experimental research with quai experimental method using 9 samples for 3 treatment groups, 3 people in control group (X1), 3 experimental groups (X2), 3 experimental groups (X3), used in this study are primary data, data analysis teachnique using Analysis of Variancw (ANOVA), before doing Hypothesis test firstly test Normality and Homogeneity tes, then test Anova. Results of variance analysis. Based on the results of the date, proving that dry facial skin care without the use of white skin care mask of the watermelon fruit in the control group did not show a better result change, for the 1x3 day experimental group there were significant change as well as the 1x7 day treatment group. Hypotesis test Normality and Anova. Results of variance analysis. Based on the result of the data, proving that dry facial skin care without the use of white skin mask of the watermelon fruit in the control group did not show a better result change, for the 1x3 day experimental group. Hypothesis accepted for 0.000<0.050 and then continued with DUNCAN Test which showed significantly different groups besed on the results of the study proved white skin mask Watermelon Fruit as Dry Skin Care Treatment Mask with the best usage frequency of 1x3 days.Keywords : Watermelon Mask, Dry Skin